A comparison of nanoparticullate CpG immunotherapy with and without allergens in spontaneously equine asthma‐affected horses, an animal model. Issue 1 (1st November 2017) - Klier, John; Geis, Sabine; Steuer, Jeanette; Geh, Katharina; Reese, Sven; Fuchs, Sebastian; Mueller, Ralf S.; Winter, Gerhard; Gehlen, Heidrun
Abstract: Introduction: New therapeutic strategies to modulate the immune response of human and equine allergic asthma are still under extensive investigation. Immunomodulating agents stimulating T‐regulatory cells offer new treatment options beyond conventional symptomatic treatment or specific immunotherapy for human and equine allergic airway diseases, with the goal of a homoeostatic T‐helper cell balance. The aim of this study was to evaluate the effects of a nebulized gelatin nanoparticle‐CpG formulation (CpG‐GNP) with and without specific allergens for the treatment of spontaneous allergic equine asthma as a model for human asthma. Methods: Twenty equine asthma‐affected horses were treated either with CpG‐GNP alone or CpG‐GNP with allergens. Two specific allergens were selected for each horse based on history and an in‐vitro test. Each horse received seven administrations of the respective nebulized composition and was examined before treatment, immediately after and 6 weeks after the treatment course. Results: Clinical parameters such as breathing rate, indirect interpleural measurement, arterial blood gases, amount of tracheal mucus and percentage of neutrophils and cytokines in tracheal washes and serum samples were evaluated. Treatment with CpG‐GNP alone as well as in combinations with relevant allergens resulted in clinical improvement of nasal discharge, breathing rate, amount of secretion and viscosity, neutrophil percentage and partial oxygen pressure directly after and 6 weeks after treatment. There were no significant differences between the two treatments in clinical parameters or local cytokine profiles in the tracheal wash fluid (IL‐10, IFN‐g, and IL‐17). IL‐4 concentrations decreased significantly in both groups. Conclusion: Nonspecific CpG‐GNP‐based immunotherapy shows potential as a treatment for equine and possibly also human allergic asthma. Abstract : The aim of this study was to evaluate the effects of a nebulized gelatin nanoparticle‐CpG formulation (CpG‐GNP) with and without specific allergens for the treatment of spontaneous allergic equine Asthma as a model for human asthma. Immunomodulating agents stimulating T‐regulatory cells offer new treatment options beyond conventional symptomatic treatment for human and equine allergic airway diseases, with the goal of a homoeostatic T‐helper cell balance. Nonspecific CpG‐GNP‐based immunotherapy shows potential as a treatment for equine and possibly also human allergic asthma.